2016
DOI: 10.1016/j.ridd.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression symptomatology in adult siblings of individuals with different developmental disability diagnoses

Abstract: Factors predicting the emotional well-being of adult siblings of those with developmental disability (DD) remain under-researched. In this study adult siblings of individuals with Down's syndrome (DS), autism (ASD), Prader-Willi syndrome (PWS) and those with DD but with unknown aetiology (DUA) were compared with each other and a closely-matched control group to ascertain if sibling disability type made a difference to anxiety and/or depression levels. Also considered was the interactive effect of gender, age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…It also suggests that although anxiety symptoms may be raised in WS (Royston et al, 2017), there is no support for a social contagion model of anxiety (see Serra Poirier et al, 2017) in relation to siblings. Overall, our findings are positive, and provide further support for the argument that children with developmental disabilities are not an inevitable source of difficulty for siblings (Hastings, 2016;Hastings & Petalas, 2014;O'Neill, & Murray, 2016;Rodgers et al, 2016).…”
Section: Discussionsupporting
confidence: 80%
“…It also suggests that although anxiety symptoms may be raised in WS (Royston et al, 2017), there is no support for a social contagion model of anxiety (see Serra Poirier et al, 2017) in relation to siblings. Overall, our findings are positive, and provide further support for the argument that children with developmental disabilities are not an inevitable source of difficulty for siblings (Hastings, 2016;Hastings & Petalas, 2014;O'Neill, & Murray, 2016;Rodgers et al, 2016).…”
Section: Discussionsupporting
confidence: 80%
“…A severe and life-threatening disease has a larger impact on the psychological functioning of the healthy siblings, and their risk of having emotional and behavioral problems is 1.6-2 times greater than healthy children (27). The type and severity of chronic disease or disability of children may cause some effects that could be reflected in their respective siblings during adulthood (28,29). Based on the self-report of the healthy siblings, we found that the psychosocial health scores of the healthy siblings of the children with cerebral palsy, hematologic/oncologic disease, and asthma were significantly lower than that of the healthy siblings of healthy; the impact being most significant on the healthy siblings of children with cerebral palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Since different therapeutic approaches, the time since diagnosis, and the severity of disease/mortality may have a different impact on the QoL of the healthy siblings of children with chronic disease (26). Studies have shown that poor psychosocial functions observed in healthy siblings due to chronic disease or disability is also reflected during their adulthood (3,25,28,36,37). The relationship between the siblings is influenced by their cognitive, social, and emotional development, which are the determinants of QoL (38).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas participants who had a brother or sister with SZ had to think about their relationship with him or her when filling in the questionnaire, unselected siblings could think about any brother or sister they chose. Although our participants were matched on more variables than in previous studies comparing groups on sibling relationships [42,71,72], we did not control for either age differences between the dyads, birth order, or the number of persons in each sibship, which are liable to influence dimensions of sibling relationships [50].…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%